Pengaruh Perilaku Kepemimpinan terhadap Komitmen Anggota pada Buana Pimpinan Daerah Nasyiatul Aisyiyah Kabupaten Kendal - Dyah Pikanthi Diwanti; Nurul Aisyah; Novi Kandiyah; Putri Diana (Sekolah Tinggi Ilmu Ekonomi AMM, 2020)
This study aims to explain the influence of leadership behaviours initiating structure and consideration of the commitments member of the Regional Leadership Nasyiatul Aisyiyah Buana Kendal. This study uses a quantitative method using data primary and secondary data obtained from the results of questionnaires. The respondents who used at least 60 people. Data collection techniques using questionnaires and documentation which the sample Buana Nasyiatul Aisyiyah regional leaders Kendal district and sampling techniques using data analysis method. The tools used in this research is multiple linear regression with IBM SPSS program 16. Based on the research that has been processed indicates that the variable initiating structure leadership behaviour (X1) and consideration (X2) partially and simultaneously influence the commitment variable member of the Buana Regional Leadership Nasyiatul Aisyiyah Kendal. This study shows that the influence of the initiating structure and consideration leadership behavioural variables on organizational commitment is 50.6%, then the rest is influenced by other variables at 49.4%.